2018
DOI: 10.1177/1035304618781661
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Australian garment and childcare homeworkers’ experience of regulation and representation

Abstract: Labour markets in Australia have long been segmented by gender and race. This study compares two highly gendered and racially segmented labour markets, home-based family day care workers and garment homeworkers. The comparative cases examine the broader trends of migration, production and consumption that reinforce gender and racial stereotypes, and discourses that underpin representations that women workers are ideally suited to such work. We theorise the gender and racialised inequalities of homework based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Although informal labour contracts are more pervasive in developing countries, they are detectable in certain sectors of developed nations as well. Delaney et al (2018) show how Australian home-based garment and child-care workers receive significantly less than the statutory minimum pay, lack superannuation, and work excessive hours in risky environments with low occupational health and safety standards and no protection from unfair dismissal. At the risk of invisibilisation, contract workers everywhere are isolated and without scope for bargaining collectively.…”
Section: Introductionmentioning
confidence: 98%
“…Although informal labour contracts are more pervasive in developing countries, they are detectable in certain sectors of developed nations as well. Delaney et al (2018) show how Australian home-based garment and child-care workers receive significantly less than the statutory minimum pay, lack superannuation, and work excessive hours in risky environments with low occupational health and safety standards and no protection from unfair dismissal. At the risk of invisibilisation, contract workers everywhere are isolated and without scope for bargaining collectively.…”
Section: Introductionmentioning
confidence: 98%
“…Migrant care workers—as with non‐professional frontline care workers in general—are paid poorly (Goel & Penman, 2015). It is therefore not surprising that many care workers point to their pay as an undesirable aspect of their working conditions (Delaney et al, 2018; Gao et al, 2015; Scarino et al, 2015). Importantly, though, at least one study (Gao et al, 2015) found that the low pay was not related to care workers intentions to stay or leave the job.…”
Section: What We Already Know About the Experiences Of Migrant Care W...mentioning
confidence: 99%
“…For example, they can make an impact by fostering good relations (Goel & Penman, 2015), by providing language support (Gao et al, 2015; Goel & Penman, 2015; King et al, 2012) and by focussing on cultural diversity or improving cultural awareness (Gao et al, 2015; Nichols et al, 2015). Notably, home‐based child care workers report feeling particularly unsupported by their organisations (Delaney et al, 2018). Black aged care workers, similarly feel that organisations are not supporting them and ignoring racism, with a study of black carers concluding that ‘in neither account is there a strong indication that supervisors and managers actively sought changes in client behaviour or demanded that African migrant care workers be respected’ (Olasunkanmi‐Alimi et al, 2021).…”
Section: What We Already Know About the Experiences Of Migrant Care W...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, contracting is standard; family day care educators are almost universally self-employed and set their own fees. For further discussion of family day care workers' employment arrangements, see Delaney et al (2018). help educators' families understand the nature of the work, provide practical resources such as equipment and toy libraries and organise play sessions to bring together groups of educators and the children for whom they care.…”
Section: Family Day Care In Australia: a Distinctive Model Of Coregul...mentioning
confidence: 99%